Changes in Alkaline Ribonuclease Activity During Compensatory Renal Growth - Rosso, Pedro (1973)
Unilateral nephrectomy in rats produces an increase in ribonuclease activity in both nuclear and cytoplasmic fractions of the contralateral kidney. The timing of this increase and the changes in the proportion of free activity to protein-bound activity are different in each fraction. A peak in inhibitor-bound ribonuclease, suggesting a higher amount of inhibitor, was found in the cytoplasmic fraction before the increase in RNA/DNA ratio. Ninety-six hours after the operation, ribonuclease was still significantly increased in both the nuclear and cytoplasmic fractions. The inhibitor-bound activity was increased in proportion to cellular RNA, maintaining a ribonuclease activity per μg of RNA similar to the controls.